Cognitive Flexibility Predicts PTSD Symptoms: Observational and Interventional Studies - Ben-Zion, Ziv; Fine, Naomi B.; Keynan, Nimrod Jackob; Admon, Roee; Green, Nili; Halevi, Mor; Fonzo, Greg A.; Achituv, Michal; Merin, Ofer; Sharon, Haggai; Halpern, Pinchas; Liberzon, Israel; et al. (Frontiers in Psychiatry, 2018)
Introduction: Post-Traumatic Stress Disorder (PTSD) is a common and severe psychiatric disorder with profound public health impact due to its high prevalence and debilitating nature. The first period after trauma exposure is a critical period to evaluate individuals at risk of prolonged PTSD. Neurobehavioral dimensions of the response to trauma exposure may help identify survivors at high risk, as well as developing novel, mechanism-based early interventions. We hypothesized that better neurocognitive functions one month after trauma would predict less severe PTSD symptoms a year post trauma exposure, and that early neurobehavioral intervention would improve neurocognitive domains, later to be evident in clinical amelioration. Methods: To longitudinally evaluate neurocognitive and clinical dimensions of responses to traumatic events and to uncover underlying cognitive mechanisms of clinical symptoms, we used two large independent samples. In the first observational sample, we prospectively tracked clinical symptoms and cognitive functioning in 181 trauma-exposed individuals admitted to an hospital Emergency Room (ER), at one-, six-, and fourteen months following trauma exposure (‘Study 1’). In the second interventional sample, we longitudinally followed 87 recent trauma survivors, randomly allocated to either web-based neurocognitive training (n=50), which included classic paradigms used in cognitive neuroscience and executive function batteries, or control tasks (n=37). Similarly, we evaluated participants’ clinical condition and neurocognitive functions at one- and three months after trauma exposure (pre-and post-intervention), and at six-month after trauma admission, using an identical recruitment and evaluation methodology (‘Study 2’). Results: Consistent with our main hypothesis, individuals with higher cognitive flexibility scores one-month after trauma showed significantly less severe PTSD symptoms at 14 months post-trauma (p=0.002). Consistent with our auxiliary hypothesis, improvement in cognitive flexibility following the intervention was significantly higher than improvement in control groups (p=0.019), and was associated with reduced PTSD symptoms at six-months post-trauma (p=0.017). Furthermore, the magnitude of improvement in cognitive flexibility post-intervention was significantly positively correlated with the subsequent clinical improvement (p=0.002). Discussion: Our findings suggest that cognitive flexibility assessed post-trauma predicts PTSD symptoms in the first critical year, and demonstrates the effectiveness of early cognitive intervention. These findings may guide personalized mechanism-driven early interventions for acute PTSD individuals.